A modernized version of a 1D soil vegetation atmosphere transfer model for improving its future use in land surface interactions studies. (April 2017) - Anagnostopoulos, Vasileios; Petropoulos, George P.; Ireland, Gareth; Carlson, Toby N.
Abstract: SimSphere is a land biosphere model that provides a mathematical representation of vertical 'views' of the physical mechanisms controlling Earth's energy and mass transfers in the soil/vegetation/atmosphere continuum. Herein, we present recent advancements introduced to SimSphere code, aiming at making its use more integrated to the automation of processes within High Performance Computing (HPC) that allows using the model at large scale. In particular, a new interface to the model is presented, so-called "SimSphere-SOA" which forms a command line land biosphere tool, a Web Service interface and a parameters verification facade that offers a standardised environment for specification execution and result retrieval of a typical model simulation based on Service Oriented Architecture (SOA). SimSphere-SOA library can now execute various simulations in parallel. This allows exploitation of the tool in a simple and efficient way in comparison to the currently distributed approach. In SimSphere-SOA, an Application Programming Interface (API) is also provided to execute simulations that can be publicly consumed. Finally this API is exported as a Web Service for remotely executing simulations through web based tools. This way a simulation by the model can be executed efficiently and subsequently the model simulation outputs may be used in any kind of relevant analysis required. The use of these new functionalities offered by SimSphere-SOA is also demonstrated using a "real world" simulation configuration file. The inclusion of those new functions in SimSphere are of considerable importance in the light of the model's expanding use worldwide as an educational and research tool. Highlights: Application Programming Interface (API) is now provided to execute SimSphere. A Service Oriented Architecture with Web Service interface added to SimSphere. SimSphere becomes now suitable for HPC use. Developments vital in its future use as standalone tool and for its synergy with EO data.